2021
DOI: 10.35808/ersj/2374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Enterprises’ Readiness in for Industry 4.0 Implementation: The Case of Poland

Abstract: Purpose: The paper aims to analyze the readiness of enterprises in Poland for industry 4.0 implementation with taking into consideration its barriers as well reasons of implementing industry 4.0. Design/Methodolology/Approach: The research was conducted by means of diagnostics opinion CAWI (Computer Assisted Web Interview) questionnaire. The research was conducted by means of diagnostics opinion CAWI (Computer Assisted Web Interview) questionnaire among 40 respondents (owners/employees) of enterprises located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Companies' considerable participation in CSR programs will improve their reputation among consumers and society. The authors plan to investigate not only employee perception but also client perception from the CSR perspective in the future in the aspect of sustainability as well as industry 4.0 technologies and society 5.0 requirements (Rosak-Szyrocka et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Companies' considerable participation in CSR programs will improve their reputation among consumers and society. The authors plan to investigate not only employee perception but also client perception from the CSR perspective in the future in the aspect of sustainability as well as industry 4.0 technologies and society 5.0 requirements (Rosak-Szyrocka et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…In the era of globalisation of economic activities and open market economy systems, companies compete with each other by improving logistics, which significantly affects the efficiency of operations. In today's world, an excellent logistics system acts as a decisive factor in competition in the markets, both nationally and internationally (Rosak-Szyrocka, Żywiołek, Kulińska, and Matulewski, 2021).…”
Section: Building a Supply Chain Model For The Furniture Industrymentioning
confidence: 99%
“…Apart from this, there was greater speed and agility of operations. The survey of RosakSzyrocka et al (2021) in Poland showed that the main barrier to the implementation of Industry 4.0 in companies is low awareness, high cost, and a lack of support for implementing the concept. Regarding Czechia, Krajčík (2021) ex amined the digitalization of SMEs and found a slow transition, lack of strategy, and lack of funds.…”
Section: Theoretical and Literature Reviewmentioning
confidence: 99%